Kualitas Hidup Penderita Gagal Jantung Kongestif Berdasarkan Derajat Kemampuan Fisik dan Durasi Penyakit - Saida Saida; Haryati Haryati; La Rangki (Universitas Faletehan, 2020)
Congestive Hearth Failure is a progressive syndrome that can reduce the quality of life, influenced by several internal and external factors.This study aims to determine the factors that relate to the quality of life of patients with congestive heart failure based on the level of physical ability and duration of illness.This study isanalytical with a cross-sectional design of 104 congestive heart failure patients who seeked treatment at cardiac clinic of Kendari Regional General Hospital.The sampling technique ispurposive sampling based on predetermined criteria. The quality of life was measured by usingMinnesota Living with Heart Failure questionnaire. The data analysis used chi-square statistical test with confident interval 95% (alpha 0.05). The results of study showed that most of the respondents have a good quality of life as many as 93 people (89.4%), the low level of physical ability as many as 69 people (66.3%), and the duration of illness £5 years as many as 86 people (82.7%). The bivariate analysis results showed that the level of physical ability is related to the quality of life (p-value 0.000) while the duration of illness is not related to it(p-value 1.000). To conclude, the Level of physical ability is a factor related to the quality of lifeof patients with congestive heart failure, but the duration of illness is not related.